3D spatial measurement for model reconstruction: A review. (15th February 2023) - Flores-Fuentes, Wendy; Trujillo-Hernández, Gabriel; Alba-Corpus, Iván Y.; Rodríguez-Quiñonez, Julio C.; Mirada-Vega, Jesús E.; Hernández-Balbuena, Daniel; Murrieta-Rico, Fabian N.; Sergiyenko, Oleg
Abstract: The measurement of 3D spatial coordinates for model reconstruction through artificial machine vision systems based on optical sensors and the corresponding signal processing associated with algorithms is a powerful module for cyber systems. It provides an efficient, functional, and intelligent vision and data information of the objects and scenes under observation for decisions, as well as for remote environment interactivity and autonomous robot systems actuation. Over the past 20 years, the artificial machine vision has benefited from emerging technology and a promising huge potential is peeking out, but also technical difficulties achieving customized and true commercial applications. This paper reviews the research progress, trends, and future research directions; the state-of-the-art of topics related to the 3D spatial measurement for model reconstruction. It classifies the technology by its fundamental principles and applications, to construct an outlook about its advantages, disadvantages, and challenges. Highlights: Topics related to the 3D spatial measurement for model reconstruction. Review of the research progress and the state of the art of topics. State of the art and the fundamental principles of topics detailed explanation. Description of technologies and applications are presented. Classification of technology based on optical sensors and its signal processing. Technology outlook construction advantages, disadvantages, advances, and challenges. This literature point out the emergence and boost the machine vision for innovation. Machine vision based cyber-systems contribution to industry 4.0. Literature for promotion and encourage of research in related fields.